PENGARUH IKLIM ORGANISASI DAN KOMPENSASI TERHADAP KEPUASAN KERJA PEGAWAI NEGERI SIPIL KANTOR CAMAT KATEMAN - jurnalmap map (MAP (Jurnal Manajemen dan Administrasi Publik), 2022)
The purpose of this study is to describe the organizational climate and compensation for its effect on job satisfaction of civil servants in the Kateman sub-district office. This research is a quantitative descriptive study. The number of samples is 40 respondents. The results showed that the organizational climate had a partial effect on employee job satisfaction. Compensation has a partial effect on employee job satisfaction. Organizational climate and compensation simultaneously have a positive and significant effect on employee job satisfaction. The results of the coefficient of determination test indicate that the influence of organizational climate and compensation on employee job satisfaction by 85%, while the remaining 15% can be explained by other variables outside of the research variables.